Pengembangan Bahan Ajar IPA melalui Pendekatan STEAM untuk Meningkatkan Hasil Belajar pada Siswa Adi Widya Pasraman - N. Selvia Asta Mariyana; Herlina Usman (Cetta: Jurnal Ilmu Pendidikan, 2023)
This research conducted because of the lack of teaching materials in general subjects, especially science, at Adi Widya Pasraman. This research aims to develop science-teaching materials using the steam (science, technology, engineering, art, and math) approach to improve students learning outcomes at Adi Widya Pasraman. The method used in this research is Research and Development, with the ADDIE (analysis, design, development, implementation, evaluation) approach. The stages in the ADDIE approach (analysis, design, development, implementation, evaluation) namely needs analysis, designing teaching materials, developing teaching materials, implementation and evaluation. The teaching material product that will developed in this research is a Google web site, which can accessed via gadgets or computers. This research carried out at Adi Widya Pasraman in East Kolaka Data collection carried out through observation, interviews, tests, and questionnaires. Data analyzed using validation, evaluation, revision and implementation stages. The results of this research are in the form of needs analysis data, where students really need teaching materials in general learning, which can be accessed easily, and contain material that is adaptive to education at Adi Widya Pasraman, and is easy to implement for students. Based on the needs analysis and literature study carried out, the STEAM (science, technology, engineering, art, and mathematics) based science teaching materials at Adi Widya Pasraman are very feasible.